SEXUAL VIOLENCE AND HARASSMENT IN ISLAMIC BOARDING SCHOOLS (PONDOK PESANTREN) IN THE CONSTRUCTION OF INDONESIAN MEDIA DISCOURSE - Putri, Sekar; Yera Yulista; Achmad Syarifudin (MEDIOVA: Journal of Islamic Media Studies, 2025)
This research started from the problem of reporting about cases of violen and sexual harassment in Islamic boarding schools which were highlighted by the mass media which gave rise to various negative opinions from the public towards Islamic boarding schools. The aim of this research is to find out and analyze news in mainstream mass media regarding discourse on violen and sexual harassment in Islamic boarding schools. The method used is a qualitative method of critical discourse analysis using Teun A. Van Dijk’s theory. The research results show that the kompas.com media generally emphasizes the issues of sexsual harassment committed by Islamic boarding school leaders, the news is more dominant about the actions taken by several individuals in handling and disclosing the case. Meanwhile, on kumparan.com media, reports questioned the performance, seriousness and understanding of the ministry of religion regarding the rise in cases of abuse in Islamic boarding schools. The news text further explains the many cases of sexual abuse committed by Islamic boarding school leaders or caregivers at Islamic boarding schools. Keywords: Sexsual Harrasment, Islamic Boarding School, Mass Media, Critical Discourse Analysis